A Her2-let-7-β2-AR circuit affects prognosis in patients with Her2-positive breast cancer. Issue 1 (December 2015) - Liu, Dan; Deng, Que; Sun, Limin; Wang, Tao; Yang, Zhengyan; Chen, Hongyu; Guo, Liang; Liu, Yanjun; Ma, Yuanfang; Guo, Ning; Shi, Ming
Abstract Background Our previous studies show that β2-adrenergic receptor (β2-AR) is highly expressed in most Her2-overexpressing breast cancers. However, the mechanisms underlying upregulation of the β2-AR expression in Her2-overexpressing breast cancer cells are not fully understood. The clinical significance of the β2-AR overexpression in breast cancer is unclear. Methods Human breast cancer cells MCF-7 and MCF-7/Her2 were transfected with the let-7 mimics or inhibitors. The expression of β2-AR was analyzed by Western blot. The β2-AR status in primary and metastatic sites of breast cancer and the human breast cancer tissue microarrays containing 49 primary tumors and 50 metastatic lymph node tissues was analyzed by immunohistochemistry. The correlation of lymph node metastasis with the β2-AR level was determined in 59 primary tumor tissues from the patients with Her2-positive breast cancer. The clinical prognostic significance of the β2-AR overexpression in the patients with Her2-positive breast cancers was evaluated by a retrospective study. Results The let-7f level in Her2-overexpressing breast cancer cells SKBR3 and BT474 was significantly lower than that in MCF-7 cells, which express low level of Her2. Ectopic expression of Her2 in MCF-7 cells (MCF-7/Her2) represses the expression of microRNA let-7f, which is previously identified to regulate baseline β2-AR expression. The treatment with MEK1/2 inhibitors PD98059 or PD184352 effectively restored the let-7f level, suggesting that Her2-overexpression-mediated ERK constitutive activation inhibited let-7f, leading to the upregulation of the β2-AR expression. The transfection with the let-7f mimics markedly downregulated the β2-AR level, whereas the let-7 inhibitor significantly upregulated the β2-AR expression in both parental MCF-7 and MCF-7/Her2 cells. In addition, treatment of MCF-7/Her2 cells with isoproterenol resulted in a concentration-dependent reduction of the let-7f expression, demonstrating that the inhibitory effect of Her2 overexpression on let-7f can be reinforced by agonist-triggered β2-AR activation. We further demonstrate that high level of β2-AR associates with lymph node metastasis and poor outcome in the patients with Her2-positive breast cancer. Conclusions The mutual and reciprocal interaction between Her2, β2-AR, and let-7f may maintain a high level of β2-AR in breast cancer cells. Our data suggest that β2-AR may be a new useful biomarker for predicting prognosis in Her2-positive breast cancer and may also be a promising selective therapeutic target for the aggressive subtype of breast cancer.